PHILOSOPHICAL CHARACTERISTICS OF SOCIAL MODERNIZATION PROCESSES IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article examines the theoretical and methodological foundations for researching social modernization processes, provides a philosophical analysis of these processes, and explores their strategic significance. Additionally, the philosophical characteristics of social modernization processes are analyzed.